El Comportamiento Etnocentrista De Los Consumidores Jóvenes En Saltillo, Coahuila - Wong, Adriana Méndez; Garcés, Elizabeth Ana Aguilar; Cavazos, Juana Alicia Villarreal; Ramírez, Frida María Martínez (European Scientific Journal, ESJ, 2018)
This paper focuses on identifying the young people that show predisposition when consuming foreign products. A Cestscale instrument was applied (Consumer Ethnocentric Tendencies Scale) and developed by Tetence A. Shimp and Sharma S. (1987), and was quoted by Schiffman and Lazar Kanuk (2010). The questions were categorical and the answers were pointed on a Likert scale from 1 to7. The study is descriptive and exploratory with a transversal no experimental measurement. 103 valid polls were obtained with a rate of 95% validating the 17 items instrument with a Cronbach Alpha of 0- 870. The study results show that the interviewed population considered themselves as an ethnocentric buyer. This is because it evaluated the answers to the variant to be high. Also, it statistically confirms that there are no meaningful differences between men and women in regards to their ethnocentric characteristics.